NADPH oxidase derived reactive oxygen species are involved in human neutrophil IL-1β secretion but not in inflammasome activation - Gabelloni, María Laura (2013)
Neutrophils are essential players in acute inflammatory responses. Upon stimulation, neutrophils activate NADPH oxidase, generating an array of reactive oxygen species (ROS). Interleukin-1 beta (IL-1β) is a major proinflammatory cytokine synthesized as a precursor that has to be proteolytically processed to become biologically active. The role of ROS in IL-1β processing is still controversial and has not been previously studied in neutrophils. We report here that IL-1β processing in human neutrophils is dependent on caspase-1 and on the serine proteases elastase and/or proteinase 3. NADPH oxidase deficient neutrophils activated caspase-1 and did not exhibit differences in NALP3 expression, indicating that ROS are neither required for inflammasome activation nor for its priming, as has been reported for macrophages. Strikingly, ROS exerted opposite effects on the processing and secretion of IL-1β; whereas ROS negatively controlled caspase-1 activity, as reported in mononuclear phagocytes, ROS were found to be necessary for the exportation of mature IL-1β out of the cell, a role never previously described. The complex ROS-mediated regulation of neutrophil IL-1β secretion might constitute a physiological mechanism to control IL-1β-dependent inflammatory processes where neutrophils play a crucial role.